Study of greenhouse gases in the bottom-water-atmosphere system in coastal marine ecosystems of Kievka Bay, Sea of Japan - Yatsuk, Andrey; Nesterova, Olga; Bovsun, Mariia (Edelweiss Applied Science and Technology, 2025)
The paper presents for the first time the results of gas geochemical studies in the bottom-water-atmosphere system of coastal-marine ecosystems of Kievka Bay and the adjacent shelf. Regional estimates of methane and carbon dioxide content in bottom sediments, the water column and the near-water atmosphere were obtained. The maximum methane content up to 447 nmol/l was established in the bottom sediments of the central part of the bay, the place of accumulation of organic saturated fine-grained silt sediments, and the minimum in the open part of the sea. Methane concentrations in water varied from 2.6 to 17.5 nmol/l, with maxima in the surface horizons of the central part of the Kievka Bay water area. CO2 concentrations in the near-water layer of the atmosphere varied in the range from 422.10 to 477.37 ppm, averaging 426.56 ppm. The concentration of CH4 varied from 2.029 to 2.070 ppm, averaging 2.032 ppm. The methane flux at the water-atmosphere boundary varied from 0.01 to 18.10 mol/km2 day, averaging 2.7 mol/km2 day. The increased concentrations and fluxes of methane in the surface horizons of the shallow waters of Kievka Bay and the decreased salinity values indicate the influence of the river runoff of the Kievka River, as well as the potential influence of shelf bottom sediments. In general, the studies revealed methane emissions into the atmosphere of varying intensity (from weak to high), which characterizes Kievka Bay as a low-intensity source of methane entering the atmosphere during the autumn transition period of the year.